Effect of switching from prior Nucleos(t)ide Analogue(s) to Tenofovir alafenamide on lipid profile and cardiovascular risk in patients with Chronic Hepatitis B - Witchayaporn Praguylertluck; Apichat Kaewdech; Naichaya Chamroonkul; Teerha Piratvisuth; Pimsiri Sripongpun (PLoS ONE, 2025)
Introduction Tenofovir alafenamide (TAF) is recommended for chronic hepatitis B (CHB) treatment in international guidelines according to its efficacy and safety. However, in phase III study, an increased LDL-c was observed in those who were switched from Tenofovir disoproxil fumarate (TDF) to TAF. Limited data exists on whether lipid profiles change only in individuals who switched to TAF from TDF or from any nucleoside/nucleotide analogues (NUC). We investigated how switching to TAF affected lipid and cardiovascular outcomes in Thai CHB patients. Materials and methods We conducted a prospective observational study including CHB patients who had to switch from their prior NUC to TAF according to the national reimbursement policy in late 2022. All enrolled patients had lipid tests and transient elastography (TE) done at 0 and 48-week post-switch to TAF. Demographic data, prior NUC, liver biochemistry, controlled attenuated parameter (CAP) and liver stiffness (elastic modulus; E) data measured by TE were collected. The changes in lipid, Thai cardiovascular (CV) risk score, and TE results between 0 and 48-week were compared. Results A total of 110 patients who were switched to TAF and completed 48-week follow-up were analyzed. The prior NUCs were as follows: 47 Lamivudine (LAM), 22 Entecavir (ETV), and 41 TDF-based. Baseline characteristics were similar between the three groups except for underlying hypertension was more frequent and baseline total cholesterol was lower in the TDF-based group. At 48-week post-switch, the median LDL-c changes were -2.45, -5.9 and +8.8 mg/dL (p<0.001), and total cholesterol changes were -4.5, -4 and +17 mg/dL (p<0.001), in the ETV, LAM, and TDF-based group, respectively. Whereas the changes in hepatic steatosis (measured by CAP), and liver stiffness (measured by E) as well as Thai CV risk score were not significantly different. No cardiovascular events occurred during follow-up. Conclusion Significant increase in LDL-c and total cholesterol after switching to TAF were observed only in patients with prior TDF, but not in those with prior ETV or LAM. Careful monitoring of lipids after the switch may not be universally needed. Data regarding long-term cardiovascular outcomes are warrant.